2017
DOI: 10.1007/s11403-017-0211-6
|View full text |Cite
|
Sign up to set email alerts
|

Exponential structure of income inequality: evidence from 67 countries

Abstract: Economic competition between humans leads to income inequality, but, so far, there has been little understanding of underlying quantitative mechanisms governing such a collective behavior. We analyze datasets of household income from 67 countries, ranging from Europe to Latin America, North America and Asia. For all of the countries, we find a surprisingly uniform rule: Income distribution for the great majority of populations (low and middle income classes) follows an exponential law. To explain this empirica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 64 publications
1
42
0
1
Order By: Relevance
“…Among them, the distribution of income and wealth in a society was known to follow a power-law by V. Pareto in 1897 [ 1 ] and, since then, many empirical and numerical studies have been performed and newly discovered facts are reported over the whole range distribution functions [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. The so-called Pareto law is valid only for the high rich people [ 9 , 10 , 11 , 12 ] and for the majority of non-rich people different distributions such as exponential and/or gamma-like functions are well fitted to the empirical statistics [ 13 , 14 , 15 ]. To explain the observed features of distributions of income and wealth, several agent-based models have been proposed on the basis of stochasticity and statistical mechanics.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the distribution of income and wealth in a society was known to follow a power-law by V. Pareto in 1897 [ 1 ] and, since then, many empirical and numerical studies have been performed and newly discovered facts are reported over the whole range distribution functions [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. The so-called Pareto law is valid only for the high rich people [ 9 , 10 , 11 , 12 ] and for the majority of non-rich people different distributions such as exponential and/or gamma-like functions are well fitted to the empirical statistics [ 13 , 14 , 15 ]. To explain the observed features of distributions of income and wealth, several agent-based models have been proposed on the basis of stochasticity and statistical mechanics.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from advanced economies shows a well‐defined two‐class structure. The majority of the population (about 97%) belongs to the lower class characterized by the exponential (“thermal”) distribution, whereas the upper class (about 3% of the population) is characterized by the Pareto power‐law (“superthermal”) distribution, and its share of the total income expands and contracts dramatically during booms and busts in financial markets (Tao et al., ).…”
Section: Uncertainty Measurement In Economic Disparitymentioning
confidence: 99%
“…A jövedelmek eloszlása ettől lényegesen eltérő, exponenciális (hat-vány)eloszlást követ, melynek kumulatív eloszlásfüggvényét a 3.b ábra mutatja. A jövedelmi egyenlőtlenség exponenciális struktúráját egy, a közelmúltban megjelent, hatvanhét országra kiterjedő elemzés is igazolta (Tao et al, 2017).…”
Section: áBraunclassified